PENGARUH PENGGUNAAN STATIN TERHADAP TINGKAT KEPARAHAN PASIEN COVID-19 DENGAN KOMORBIDITAS: Sebuah Tinjauan Sistematis - Mawar Izzati Nadilla (2023)
Introduction: The severity of COVID-19 patients is influenced by several things, one of which is comorbidity. The most common comorbidities are atherosclerosis and hypertension associated with endothelial dysfunction. Several studies stated that one of the drugs routinely used by comorbid patients, statins, has a pleiotropic effect as an anti-inflammatory and vasculoprotector. We are interested in examining the effect of statin use on the severity of COVID-19 patients with comorbidities through four indicators, there are clinical symptoms, need for mechanical ventilation and intensive care units, and CRP levels. Methods: A systematic review using secondary data from literature obtained from the Google Scholar, EBSCO, Science Direct, and Pubmed databases using the PRISMA method from July 2022 to January 2023. Results: Eight journals reviewed, four of them stated that statins had an effect in reducing the severity of COVID-19 patients with comorbidities, three journals did not find a significant difference in severity, and one journal showed that statins increased the severity of COVID-19 patients with comorbidities. Conclusion: The use of statins can reduce the severity of COVID-19 patients with comorbidities.